Controversies around the Transatlantic Trade and Investment Partnership - Jasiak, Kinga (Wydawnictwo Naukowe WNPiD UAM, 2018)
Negotiations on the Transatlantic Trade and Investment Partnership between the European Union and the United States have been in progress since 2013. The European Commission published the first document on the status of negotiations one year later. The main aim of this paper is to present TTIP as a very controversial agreement, both in the view of scholars and the international public. Negotiations behind closed doors, the growing democratic deficit, the investor-state dispute resolution mechanism (ISDS), and the European Citizens’ Initiative “Stop TTIP” are the most important issues in the public debate on the transatlantic agreement.
Keywords: TTIP; Controversies; ISDS; European Union; Mysterious trade agreement